The American Dream: Narratives of Space and Place in Second Life - Ferreira, Cátia (2015)
Second Life is one of the most complex virtual worlds available due to one of its main components – user-generated content. In Second Life players are active contributors to in-world development, and only 1% of the contents available were created by Linden Lab; players are not only contributing to space, but also to its social development. Some researchers suggest that Second Life's development history reflect California's one; not only because Linden Lab is a Californian company, but mainly because Second Life is announced as “your world, your imagination”, reflecting at the same time the “Californian ideology” (Barbrook and Cameron, 2001; Boellstorff, 2008) and the chasing for the American dream. The aim of this paper is to verify if Second Life's development may be considered a remix of the chasing of American dream by understanding how users are taking advantage of the building tools available, creating their own virtual places and fulfilling their own wishes. To accomplish this goal a qualitative methodology was used based on a multimodal netnographic research (Kozinets, 1998, 2002, 2006, 2010). The data collection methods were auto-netnography (Kedzior and Kozinets, 2009) and detailed observational data collection of 64 in-world locations.